2005
DOI: 10.1017/s0952836905006710
|View full text |Cite
|
Sign up to set email alerts
|

Feeding success of African wild dogs ( Lycaon pictus ) in the Serengeti: the effects of group size and kleptoparasitism

Abstract: Longer-term ecosystem level dynamics are often neglected in conservation studies involving single species. In this study, a retrospective analysis is presented on the feeding performance of African wild dogs Lycaon pictus in the Serengeti in relation to a competing species, the spotted hyena Crocuta crocuta, to test whether hyenas had an effect on feeding performance of wild dogs in this ecosystem. Our analysis is based on observations of over 700 wild dog kills recorded over a 20-year period (from 1964 to 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 28 publications
2
72
0
Order By: Relevance
“…As in the lynx case, bear kleptoparasitism could be quite costly during the wolf pup nursing period, when a continuous food supply is needed and fewer members of the wolf pack are available for hunting. Such an effect might be larger for small wolf packs and it has been shown that the effects of kleptoparasitism differ in relation to group size of the affected species (Carbone et al 2005). Loss of food to scavengers is indeed important for wolf foraging ecology.…”
Section: Discussionmentioning
confidence: 99%
“…As in the lynx case, bear kleptoparasitism could be quite costly during the wolf pup nursing period, when a continuous food supply is needed and fewer members of the wolf pack are available for hunting. Such an effect might be larger for small wolf packs and it has been shown that the effects of kleptoparasitism differ in relation to group size of the affected species (Carbone et al 2005). Loss of food to scavengers is indeed important for wolf foraging ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the densities and behaviour of wild dogs are negatively affected by the presence of other carnivore species in the Serengeti National Park (Estes & Goddard, 1967). Lions may directly cause pup mortality in wild dogs (Creel & Creel, 1996), and spotted hyaenas follow wild dogs hunting and steal their kills (Estes & Goddard, 1967;Creel & Creel, 1996;Carbone et al, 1997Carbone et al, , 2005. For these reasons wild dogs are normally found in areas with low densities of other carnivores (Creel & Creel, 1996;Vucetich & Creel, 1999).…”
Section: Incidences Of Attack By Wild Dogs and Other Carnivoresmentioning
confidence: 99%
“…Group size, for instance, can affect a group's success and the fitness of group members [10,11]. Larger groups have been shown to yield higher survival [12,13], higher reproductive output [14,15] and better foraging success [16,17] to group members in a wide range of animals. In cooperatively breeding species, increased cooperation levels are expected to enhance group performance [10], and indeed greater numbers of helpers often increase the reproductive output of groups [18][19][20].…”
Section: Introductionmentioning
confidence: 99%